THE EFFECT OF ENERGY SUPPLY AND WELFARE ON PRODUCTIVITY AND REPRODUCTIVITY HEIFERS MEAT POLL SYMNETALU NEW GENERATION - Калинка, А. К.; Гончар, В. І.; Приліпко, Т. М. (Podilian Bulletin: Agriculture, Engineering, Economics, 2016)
The results of studies using the same type of feeding in summer with different technologies in maintenance productivity and reproductivity beef heifers poll symentalu new generation in the Carpathian region of Bukovyna. It was established that during the summer for 122 days’ average daily growing heifers 1st experimental group were - 864.7 g, 127 g (11.7%) (P> 0.005) than the peers’ control group. The costs of experimental animals feed mainly 8,6kh period amounted to. From., Which is 1.6 kg for. Units. (7.9%) less than the control. Within 29 days of the final period increments heifers experimental group (Loose maintenance), average amounted to -896.5 g, 190.0 g at (12.6%)% (P> 0.005) than the control group of peers’ attachable maintenance, which were adopted in the diet in the economy. The cost of feed experimental animals in the final period accounted for 8,9kh. Units. That 2,4kh to. Units. (7.9%) less than the control. During this period of research heifers live weight was on 28,5kh (11.0%) more than the control group. It was established that growing heifers on the same type of feed for different technologies keeping Bukovyna zonal type of meat in the Loose symentalu content on the stern platform in the summer, average daily gain increased by 12.6%, making this technology beef economical, profitable and perspective in modern conditions of doing beef cattle in the absence of appropriate animal feed premixes and foothill areas in terms of the Carpathian region of Ukraine. Consumption per 100 kg live weight of dry matter in heifers experimental group (Loose maintenance) basically run is 3.1 MJ, MJ which is 0.2 less than the control group peers.